Correction: Static phase transfer catalysis for Williamson reactions: pickering interfacial catalysis. Issue 15 (10th July 2019) - Zhao, Qiangqiang; Zhao, Xiao; Peng, Hui; Liu, Yang; Yang, Lihui; Sun, Jie; Yang, Lei; Shen, Yifeng
Abstract : Correction for 'Static phase transfer catalysis for Williamson reactions: pickering interfacial catalysis' by Qiangqiang Zhao et al., Catal. Sci. Technol., 2019, 9, 3445–3453.